Carta de J. Enamorado Cuesta a Roberto H. Todd - Enamorado Cuesta, J.; Todd, Roberto H. (My University, 1941)
Carta relacionada a la bandera puertorriqueña de 1895
Keywords: Flags--Puerto Rico.; Bandera--Puerto Rico.